Partisipasi Masyarakat dalam Pengelolaan Keuangan Desa - Remensye Venzka Afrilya Nikijuluw; Saartje Sarah Alfons; Revency Vania Rugebregt (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: The village financial management is important so that the village communities have confidence in the village officials and village leaders.Purposes of the Research: To find out the form of community participation in village financial management and to see the consequences of the community's non-involvement in village financial management. Methods of the Research: This research is a normative legal research. In this study, the approach used is the legal approach. Sources of data obtained are primary legal materials and secondary legal materials. The technique of collecting legal materials is by means of library research by collecting materials through invitations, reference books, mass media, such as newspapers. The overall data in this study were analyzed qualitatively.Results of the Research: The results of this study indicate that the community has an important role in managing village finances but in practice the community involvement has not been maximized because in the process the theory used is considered low, such as manipulated community involvement, the community is considered as informing in the sense of knowing people's programs and not providing input on the program. village government. And the non-involvement of the community itself has legal consequences if in its implementation it does not involve the community, one of the evidences of cases of village financial corruption that has resulted in the conviction of various village officials who are unable to take responsibility for their actions, this is clearly due to a lack of supervision from the community.